1999
DOI: 10.1037/0278-7393.25.4.963
|View full text |Cite
|
Sign up to set email alerts
|

Rate of forgetting in amnesia: II. Recall and recognition of word lists at different levels of organization.

Abstract: Amnesic rate of decline of free recall, cued recall, and recognition of word lists with different levels of organization was investigated in 2 experiments. In Experiment 1, it was found that amnesic free recall of semantically related word lists declined at an accelerated rate, whereas free recall of lists of unrelated words declined at a normal rate. Cued recall and recognition performance of both kinds of word lists appeared to decline at a normal rate. In Experiment 2, the results of the free-recall and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 56 publications
4
50
0
Order By: Relevance
“…However, there is good reason to argue that the present results were not caused by consolidation deficits. As demonstrated in the studies by both Carlesimo, Sabbadini, Loasses, and Caltagirone (1997) and Isaac and Mayes (1999b), consolidation deficits usually arise only in the case of more complex associations than those used in the present study, and, if nevertheless existent, manifest in free but not in cued recall tests.…”
Section: Possible Alternative Explanationsmentioning
confidence: 84%
See 2 more Smart Citations
“…However, there is good reason to argue that the present results were not caused by consolidation deficits. As demonstrated in the studies by both Carlesimo, Sabbadini, Loasses, and Caltagirone (1997) and Isaac and Mayes (1999b), consolidation deficits usually arise only in the case of more complex associations than those used in the present study, and, if nevertheless existent, manifest in free but not in cued recall tests.…”
Section: Possible Alternative Explanationsmentioning
confidence: 84%
“…Because the results for the healthy subjects suggest that stronger category-item associations are more susceptible to incongruencies between learning and test than are weaker category-item associations, such an encoding deficit should have made our amnesics' retrieval processes fairly immune to possible negative effects of part-list cuing, particularly in the case of the weak items. Finding a larger amount of forgetting in amnesics than in controls thus indicates that the recall difference between healthy and amnesic subjects is more likely to reflect a retrieval deficit rather than an encoding deficit (see also Isaac & Mayes, 1999b, for evidence against major encoding problems in the present type of situation).…”
Section: Amnesic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to dualprocess theories of memory, recollection should be affected by certain experimental variables (e.g., levels of processing, divided attention) or subject variables (e.g., aging, brain damage) regardless of whether recollection is indexed using Our finding that free recall has an automatic component also calls into question the experimental strategy of equating free recall performance between groups on initial learning task (e.g., younger and older adults) in order to make sounder inferences. This approach of equating initial learning is often used in neuropsychological studies investigating memory performance between younger and older adults (Giambra & Arenberg, 1993;Harwood & Naylor, 1969;Wheeler, 2000), control subjects and amnesics (Isaac & Mayes, 1999;Kopelman & Stanhope, 1997), older controls and dementia patients (Kopelman, 1985;Reed, Paller, & Mungas, 1998), as well as other subject populations (DeLuca et al, 2004). For example, DeLuca et al found that subjects with chronic fatigue syndrome (and no co-morbid psychiatric disorders) took twice as many trials to learn a list of categorized words to a criterion of two perfect recalls.…”
Section: Implications Of the Finding That Automatic Processes Influenmentioning
confidence: 99%
“…More recently, Isaac and Mayes (1999) claimed that rate of forgetting is greater for amnesic patients than for controls when these subjects are tested for recall of semantically organized word lists. In contrast, rate of forgetting for free recall of unrelated words, and for recognition, did not differ for amnesics and controls.…”
Section: Dmts Performance Of Ad Patientsmentioning
confidence: 99%